2015
DOI: 10.1503/cmaj.150462
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate, heart rate variability and functional decline in old age

Abstract: E levated heart rate and reduced heart rate variability -the beat-to-beat variation in heart rate intervals -both reflect an altered balance of the autonomic nervous system tone characterized by increased sympathetic and/ or decreased parasympathetic activity.1-3 Sympathetic overactivity has been linked to a procoagulant state and also to risk factors for atherosclerosis, including metabolic syndrome, obesity and subclinical inflammation.2-4 Moreover, increased heart rate is related to atherosclerosis, not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 29 publications
3
59
0
1
Order By: Relevance
“…Resting HR has clinical utility in cardiovascular disease populations and is associated with cognitive decline in post-stroke patients and individuals with high cardiovascular risk (44,45). Limited research has examined resting HR as it relates to aging and neurodegenerative disease although 1 study found higher resting HR to predict worse functional status in older adults independent of cardiovascular disease (46). Regardless, resting HR is easily influenced by an array of external (eg caffeine) and internal (eg anxiety) stimuli, limiting its reliability, particularly in cross-sectional assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Resting HR has clinical utility in cardiovascular disease populations and is associated with cognitive decline in post-stroke patients and individuals with high cardiovascular risk (44,45). Limited research has examined resting HR as it relates to aging and neurodegenerative disease although 1 study found higher resting HR to predict worse functional status in older adults independent of cardiovascular disease (46). Regardless, resting HR is easily influenced by an array of external (eg caffeine) and internal (eg anxiety) stimuli, limiting its reliability, particularly in cross-sectional assessments.…”
Section: Discussionmentioning
confidence: 99%
“…1 High natural resting heart rate is associated with traditional risk factors for cardiovascular diseases, levels of inflammatory markers [2][3][4] and functional decline, 5 which suggests that resting heart rate might be related to the risk of various disease states. We previously found that resting heart rate was an independent predictor of total mortality related to cardiovascular disease in the general population.…”
mentioning
confidence: 99%
“…A significant negative correlation of aging with heart rate have been described by Ogliari et al in 2015. [43] In this context, several studies have suggested that age could related with RHR. [22,[44][45][46][47] We demonstrated that there is a strong negative association between aging and RHR which is independent of other cardiovascular risk factors in both sex.…”
Section: Discussionmentioning
confidence: 99%